Coroas estéticas anteriores em cerâmica metal-free: relato de caso clínico - Rossato, Desirée Mory [UNESP]; Saade, Esther Gomes [UNESP]; Saad, José Roberto Cury [UNESP]; Porto Neto, Sizenando de Toledo [UNESP] (My University, 2010)
Society's change of parameters for health and aesthetics has resulted in an increased demand for dental treatments. Nowadays, ceramics systems have shown a substantial development, becoming more reliable and predictable. Dental ceramics, besides being chemically stable, present excellent optical properties when compared to dental structures, thus assuring a special position in the list of aesthetic restorative materials. OBJECTIVE, CASE REPORT AND CONCLUSION: This article describes a successful clinical procedure involving the anterior teeth aesthetics, which were restored with all-ceramic crowns (IPS e.max® Ivoclar Vivadent).

A procura por tratamentos estéticos tem aumentado graças à conscientização da sociedade sobre a importância da saúde e da estética dental. Nos dias de hoje, tem havido um substancial desenvolvimento dos sistemas cerâmicos, tornando-os confiáveis e com resultados previsíveis. As cerâmicas dentárias, além de quimicamente estáveis, apresentam propriedades ópticas excelentes quando comparadas às estruturas dentárias, o que lhes garante um posto especial no rol dos materiais restauradores estéticos. OBJETIVO, RELATO DE CASO E CONCLUSÃO: Descrever um caso clínico com sucesso envolvendo a estética de dentes anteriores, restaurados com coroas puras de cerâmica (IPS e.max® Ivoclar Vivadent).
Aesthetic all-ceramic dental crowns for anterior teeth: a case report
Keywords: Aesthetic dental crowns; All-ceramic crowns; Coroas estéticas; Coroas puras de cerâmica